Gaining a Better Understanding of the Types of Organizational Culture to Manage Suffering at Work - Assens-Serra, Jordi; Boada-Cuerva, Maria; Serrano-Fernández, María-José; Agulló-Tomás, Esteban (Frontiers in Psychology, 2021)
Organizational culture is a central concept in research due to its importance in organizational functioning and suffering of employees. To better manage suffering, it is necessary to better understand the intrinsic characteristics of each type of culture and also its relationships with the environment. In this research, we used multiple regression analysis to analyze the capacity of eight environment variables, five business strategies and eight organizational competencies to predict the presence of Clan, Market and Hierarchy cultures (Cameron and Quinn, 1999) in a subsample of Spanish managers (n1 = 362) and a subsample of Peruvian managers (n2 = 1,317). Contrary to what most of the literature suggests, we found almost no relationship between the environment variables and the culture types. Strategy and competencies, on the other hand, do have a significant predictive capacity, showing nine links with the Clan culture, seven with the Hierarchy culture and ten with the Market culture. In conclusion, this research has found important characteristics of the types of organizational culture that could be useful to better manage suffering of employees.